Tax Compliance as a Social Norm and the Deterrent Effect of Investigations - David Ulph
In this paper we focus on the effects of investigations on tax compliance. In a very general model we explain the direct and indirect effects of investigations and analyse taxpayers’ response to an increase in the probability of audit when tax compliance is a social norm. We define the different elements that determine the impact of audits on compliance and show that if tax compliance is a social norm in the relevant community there is an additional effect arising because of social norm considerations. The behavioural response of taxpayers to an increase in the audit rate is stronger. Our Findings help explain seemingly contradictory results that emerge from the empirical evidence.tax evasion, social norm, opportunities to evade, optimal audit rule